1985
DOI: 10.1080/00223980.1985.9915452
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in the Cooperative and Noncooperative Behavior of Pairs of American Children

Abstract: Game playing behavior of same and mixed sex pairs of 5-, 8-, and 11-year-old American children was compared, using a game in which cooperative behavior maximized reward. Pairs of 8- and 11-year-old children were relatively more cooperative and attained significantly more Joint Reward Goals than 5-year-old pairs. Older pairs were not maximally cooperative, however, in terms of all the dependent measures; in adjusting for initial differences on practice trials, 5-year-olds and 8-year-olds took less time than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…That the girls showed more cooperative play than the boys in terms of latency is not really surprising. Using the same Cooperation Board, Stingle (1973) obtained the same result with dyads of a similar age (1 1 years). What is surprising-and worth further investigation-is that this main effect was revealed even though all male dyads were not equally uncooperative.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…That the girls showed more cooperative play than the boys in terms of latency is not really surprising. Using the same Cooperation Board, Stingle (1973) obtained the same result with dyads of a similar age (1 1 years). What is surprising-and worth further investigation-is that this main effect was revealed even though all male dyads were not equally uncooperative.…”
Section: Discussionsupporting
confidence: 74%
“…Studies that have focused on several age groups simultaneously in the attempt to document developmental trends in cooperative behavior offer evidence that age and sex are interacting variables. Only those subjects older than 8 years tended to show the stereotypical sex difference: Males were less cooperative than were females, as in the research of Kagan and Madsen (1972a) with 5-to 6-and 9-to 10-year-olds; Stingle (1973) with 5-, 8-, and 11-year-olds;and Vinacke and Guillickson (1964) with 7-and 14-to 16-year-olds and college students. In these studies, the youngest males and females did not seem to differ in their cooperative behavior.…”
mentioning
confidence: 88%
“…Our findings that children less than four years of age cooperate significantly less is supported by Ounsted, Cockburn & Moar 1983;Stingle & Cook 1985. They found that age was a significant factor affecting the ability of the child to cooperate.…”
supporting
confidence: 71%